TEMBANG LOKAL JAWA DI JAWA TIMUR: PERGULATAN ANTARA TRADISI DAN MODERNITAS - Afiva Nurqomariyyaha; Setya Yuwana Sudikan; Anas Ahmadi; Indayani (Jurnal Budaya Nusantara, 2023)
This study reveals the supporting aspects that make traditional Javanese songs maintained behind the splendor of modern Javanese songs in society. This study uses a qualitative design with a phenomenological approach. The research location is in East Java. Researchers collected data by means of observation, interviews, and document collection. Researchers validate data based on a triangulation system with interactive analysis. The results of the study found that traditional Javanese songs still exist in the local community because of the strong psychological ties between the people and their culture. Cultural messages can be conveyed beautifully through Javanese local songs, stimulate the imagination, and instill pleasant feelings. The implication of the findings of this study is the importance of Javanese songs to be used as a means to encourage the development of the community and culture concerned.